2000
DOI: 10.1080/02640410050074313
|View full text |Cite
|
Sign up to set email alerts
|

Children's physical activity and physical self-perceptions

Abstract: The aim of this study was to determine the relationship between physical self-perceptions and physical activity in Canadian school children aged 10-14 years. The sample consisted of 220 boys and 246 girls in grades 5-8. Physical activity was assessed by 7-day recall using the Physical Activity Questionnaire for Older Children. Self-perceptions of physical conditioning, sports competence, strength, body appearance and general physical self-worth were measured by the Physical Self-Perception Profile (PSPP). We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
157
3
25

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(206 citation statements)
references
References 5 publications
21
157
3
25
Order By: Relevance
“…These results are consistent with previous research (e.g., Crocker et al, 2000;Page et al, 1993;van de Vliet et al, 2001). The satisfactory fit of the second-order model, which included a higher-order PSW factor, supports the proposal of a general, global construct to explain adequately the relationships between the subdomain factors.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with previous research (e.g., Crocker et al, 2000;Page et al, 1993;van de Vliet et al, 2001). The satisfactory fit of the second-order model, which included a higher-order PSW factor, supports the proposal of a general, global construct to explain adequately the relationships between the subdomain factors.…”
Section: Discussionsupporting
confidence: 83%
“…For example, mirroring the documented positive effect of physical activity on self-esteem for children (Fox, 2000b;Gruber, 1986), PSP models have been found to predict between 27% and 29% of the variance in physical activity scores for boys and girls aged 10-14 (Crocker, Eklund, & Kowalski, 2000). Looking at the relationship of sport participation to self-esteem, body image and PSP, Richman and Shaffer (2000) demonstrated that pre-college sport participation for college females predicted self-esteem and that physical competence and body image mediated this relationship.…”
Section: Physical Self-perceptions Exercise Involvement and Sport Pamentioning
confidence: 99%
See 1 more Smart Citation
“…De este modo, diseñamos una escala con 45 ítems organizados alrededor de los siete ámbitos más influyentes recogidos en la literatura (GLENN;CUNNINGHAM, 2001;ILLÁN, 2011;SPIJKER;PÉREZ, 2010): salud, ocio y tiempo libre, derechos y deberes, sexualidad, empleo, integración social y educación. Obtuvimos así una escala completamente original, construida a partir de la revisión de diversas investigaciones sobre la percepción social de la discapacidad, física, sensorial y metabólica (BERNARDO; MATOS, 2003;CORREDEIRA et al, 2007;CROCKER;EKLUND;KOWALSKY, 2000), conjuntamente con el aporte de los expertos en la materia. Esta escala -y todos los ítemes que la conformanfueron sometidos a la opinión de trece expertos en discapacidad intelectual, con reconocido prestigio en el ámbito nacional e internacional, procedentes de centros de investigación superior, centros sanitarios, asociaciones y Ministerio, entre otros.…”
Section: Materials Y Métodounclassified
“…Also, boys were more physically active and had higher physical self-perceptions than girlsFespecially in the strength and sport competence subscales. 35 This may be because boys usually spend more time participating in sport and therefore report higher perceived physical competence. 7 …”
Section: Discussionmentioning
confidence: 99%